Host species of the hemiparasitic shrub Phoradendron nervosum Oliv. in densely urban areas of Quito, Ecuador. - Martín Carrera; Lía Altamirano; Karla Barragán (ACI Avances en Ciencias e Ingenierías, 2023)
Phoradendron nervosum is a hemiparasitic shrub with a wide distribution area. Despite this, the ecology of natural history of this species is not well studied. Host species of P. nervosum are reported from Mexico and Costa Rica mainly with recent reports from Ecuador. Inside the urban areas of the metropolitan area of the city of Quito, P. nervosum infects 21 species of plants, where introduced and cultivated species are more prone to infection. This study raises the reported host species of P. nervosum from Ecuador to 26 species. More sampling is needed in other areas in the wide distribution of P. nervosum to test if introduced and cultivated species are mor prone to infection and to raise the list of the host species of this common species.